Draft Seventh Five Year Plan 1985-90 and Draft Annual Plan 1985-86 Statements Union Territory of Pondicherry - Planning Commission (Planning Commission, 1985)
Draft Seventh Five Year Plan 1985 - 80 and Annual Plan 1985-86 - Heads of Development Outlay and Expenditure Draft Seventh Five Year Plan 1985-90 and Annual Plan 1985-86 Development Scheme/Projects - Outlay and Expenditure Draft Seventh/Plan 1985 -90 and Annual Peak 1985-86 Physical Targets and Achievements Draft Seventh Five Year Plan 1985-90 and Annual Plan 1985-86 Minimum Needs Programme - Outlay and Expenditure Draft Seventh Five Year Plan 1985-90 -Centrally Sponsored Schemes Outlays and Expenditure Draft Seventh Five Year Plan 1985-86 Employment Content of Sectoral Programmes 1985-90 - Outlay and Expenditure.
Government of Pondicherry, Planning and Research Department